Mapping the dynamic co-evolution of technological convergence - Wong, C.Y.; Fung, H.N. (2016)
The life cycle of product development and process innovation has been a subject of research among the innovation scholars and industrial policy makers. While the theoretical perspective of life cycle is found useful to narrate a technological and economic development process, it also inspires scholars to pursue the exploration of convergence process of different technological system and industrial agglomeration. In this paper, we present an evolutionary perspective of how patent keyword clusters evolve at ,different phases of the technological life cycle. We propose an approach to map the technological life cycle of herbal medicine - sector and explore the evolving knowledge clusters of the major industrial agglomerations in Malaysia. We perform mapping of knowledge cluster based on keywords found in the extracted patent documents, portfolio and co-patenting analysis, cross correlation analysis o~ patent classes and systematic assessment on the evolution of patenting network. For traditional medicine industry, we observe evidence of convergence of modern biotechnological methods with existing herbal medicine innovations resulting in the strengthening of patent clusters and penetration of herbal medicine in novel niches. For industrial agglomeration case, we found different convergence of innovations take place at different part of industrial clusters in Malaysia. We will highlight the functional innovation structure that is constructed based on the cooperation of three entities, university, public research institute and firm for production, research and joint knowledge creation. The evolutionary phases of development that we will articulate corresponds to the notions of how publication and patent numbers grow in sequence; and we also perceive how evolution in technological convergence relates to the technological life cycle.